2011
DOI: 10.3899/jrheum.100698
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Etanercept in Patients with Psoriatic Arthritis in a Canadian Clinical Practice Setting: The REPArE Trial

Abstract: Objective.To describe the longterm effectiveness and safety of etanercept in Canadian patients with psoriatic arthritis (PsA), treated over 24 months in clinical practice.Methods.Patients with active PsA (≥ 3 tender and ≥ 3 swollen joints) were recruited from 22 centers. Etanercept was administered at 50 mg/week subcutaneously. In addition to clinical assessment of skin and joint disease, conducted at baseline and at Months 6, 12, 18, and 24, regular patient interviews were conducted by telephone. Patient resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…These data are comparable with a previous study that looked at treatment of active PsA with etanercept over 24 months [13]. Unlike the current study, those investigators observed a nonsignificant decline in missed work days (absenteeism for any reason) from 0.7 days per 2 weeks at baseline to 0.3 days per month after 2 years of treatment (p = 0.3436).…”
Section: Discussionsupporting
confidence: 86%
“…These data are comparable with a previous study that looked at treatment of active PsA with etanercept over 24 months [13]. Unlike the current study, those investigators observed a nonsignificant decline in missed work days (absenteeism for any reason) from 0.7 days per 2 weeks at baseline to 0.3 days per month after 2 years of treatment (p = 0.3436).…”
Section: Discussionsupporting
confidence: 86%
“…Of 47 original studies, 42 included RA patients,3 11–19 21–24 26 29–40 45 46 48–53 55–64 four included psoriatic arthritis patients,20 25 27 30 two included early arthritis patients9 19 64 and three included patients with sponyloarthropathies 28 30 47. In 21 studies, RA patients satisfied the 1987 American College of Rheumatology criteria,11 13 15–17 22 23 26 32–36 41 45 46 48 51 52 54 56 60 62 in 15 studies patients were clinically diagnosed12 14 18 21 24 29 30 37–39 48 53 57–59 61 63 and in four studies patients satisfied the ICD-9 code 40 49 50 55.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies reported on early RA (<2 years) 3 11–15 23 33 34 36 41 45 54 56 59 61 62. There were 11 clinical trials,11 13 25–27 32 45 51 54 56 60 19 cross-sectional articles,3 15–17 19 24 31 33–35 47 48 50 52 55 57–59 63 15 prospective cohort articles,9 18 20 22 23 29 30 36–38 46 53 61 62 64 two case control studies14 40 and four retrospective cohort studies 21 28 39 49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gladman и соавт. [26], изучая эффективность этанерцепта у больных ПсА, определили снижение абсен-теизма по HLQ с 0,7 дня за 2 нед в начале исследования до 0,3 дня за этот же период времени через 24 мес терапии (различие, однако, не было достоверным).…”
unclassified